Addressing Comorbid Diseases in Patients with Moderate-to-Severe Psoriasis. Issue 4 (December 2013) - Yeung, Howa; Takeshita, Junko; Gelfand, Joel M.
Psoriasis is a common, chronic inflammatory skin disease that has been increasingly associated with major systemic effects. Dose-response relationships between objectively determined psoriasis severity and increased comorbid disease burden were recently demonstrated in a large, population-based study. Significant associations with cardiovascular disease, diabetes mellitus and its complications, chronic kidney disease, chronic pulmonary disease, mild liver disease, peptic ulcer disease, and rheumatologic disease were shown in patients with increasingly severe psoriasis. Future research should confirm novel comorbid disease associations and investigate the impact of psoriasis therapy on comorbid disease outcomes. For now, dermatologists, as well as primary care physicians, medical specialists, and patients suffering from moderate-to-severe psoriasis, should be aware of these associations to improve multi-disciplinary approaches for screening, monitoring, and treatment of comorbid diseases. Future evidence-based guidelines should incorporate strategies on how clinicians should address cardiovascular and other comorbid diseases, particularly for patients with more severe psoriasis.